Analisis Pengaruh Pengangguran, Tingkat Melek Huruf Dan Pdrb Terhadap Kemiskinan di Jawa Timur Tahun 2010 – 2013 - Rakhmantiyo, Dimas Tegar (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to analyze the correlations between poverty as the dependent variable and gross regional domestic product, educations which is proxied by reading ability and unemployment as the independent variable. The method used in this thesis is the Fixed Effect Model (FEM) and the software used to calculate the model are IBM SPSS 20. The data used in this thesis are panel data, which is mixed between time-series and cross section. Data between 2010 – 2013 are used and come from 38 regencies and cities in East Java. Research shows that  the independent variables (gross regional domestic product, education and unemployment) are significance and negative to dependent  variable (poverty) which mean if the rate of independent variables increased would decreased the rate of dependent variable.Keywords : Poverty, Gross Regional Domestic Product, Education, Unemplyoment